FORMULATION AND EVALUATION OF CHITOSAN NANOPARTICLES FOR IMPROVED EFFICACY OF ITRACONAZOLE ANTIFUNGAL DRUG - Y, CHARANTEJA REDDY; S, JEGANATH; KUMAR U, MUNI (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of the study was to formulate and evaluate the chitosan nanoparticles to improve the therapeutic efficacy of itraconazole by loading in nanoparticle drug delivery system. Designing the formulation of the drug itraconazole prolongs the therapeutic concentration of the drug in the blood and which will lower the frequency of dosing and also improves the efficacy of the drug. Methods: Itraconazole nanoparticles are prepared by ionic gelation method; here, chitosan is used as polymer. The formulated nanoparticles are evaluated for external morphological studies by scanning electron microscope (SEM), drug content, in vitro drug release studies, as well as infrared (IR) spectral analysis. Results: The Fourier transform IR spectra show that there was no interaction between drug and polymers; hence, they are compatible. Percentage entrapment efficiency, drug content, and percentage yield were higher for F3 formulation. The particle size analysis shows that every particle in the formulations gave the range of 148–227 nm, respectively; increasing in the particle size observed with varying concentration of polymer. SEM analysis of the nanoparticles shows that all the formulations were spherical and smooth with ideal surface morphology. As the concentration of polymer, the drug release decreased proportionally. The stability studies were carried out on the optimized formulation for 2 months at 30±2°C and 60±5% RH and 40±2°C and 75±5% RH; finally, it was observed that there was no change in drug content and in vitro drug release profile even after storage at 30±2°C and 60±5% RH and 40±2°C and 75±5% RH for 2 months. Conclusion: Itraconazole is one among the most widely used antifungal drugs. Designing the formulation of drug itraconazole prolongs therapeutic drug concentration in the blood and decreases dosage frequency and also enhances the efficacy of drug.